Ifn-g induction by the tc13tul antigen from trypanosoma cruzi in naïve balb/c mice - Tasso, Laura Mónica (2019)
Trypanosoma cruzi, the etiological agent of Chagas disease, releases factors which modulate the host immune responses, including Tc13 antigens. Regarding innate immune responses, Tc13 antigen from Tulahuén strain, Tc13Tul, has shown to induce B cell expansion and non-specific IgM production on cultures of splenocytes from naïve BALB/c mice. To obtain further information about this role, we evaluated Tc13Tul ability to induce cytokine secretion by in vitro and in vivo stimulation. In vitro Tc13Tul stimulation of splenocytes from naïve BALB/c mice induced higher IFN-g secretion than that induced by the control protein MBP (554 ± 140 pg/ml and 35.33 ± 18.56 pg/ml, respectively). Differences in neither IL-17 nor IL-4 were detected. Tc13Tul-induced IFN-? secretion was also observed in cultured naïve splenocytes from the LPS-resistant C3H/HeJ mouse strain. In vivo administration of Tc13Tul (or MBP as control) to naïve BALB/c mice (3 daily ip doses of 1 ?g/mouse/dose) increased non-specific IgG in sera. In addition, in vitro cultured splenocytes from Tc13Tul-inoculated mice secreted a higher basal level of non-specific IgM than controls and the in vitro Tc13Tul stimulation of these cells showed an additive effect on IgM secretion. Regarding Tc13Tul-induced IFN-g secretion, in vitro cultured splenocytes from Tc13Tul-inoculated mice have no differences in basal levels respect to controls; however, when splenocytes were in vitro stimulated with Tc13Tul, cells from Tc13Tul-inoculated mice showed higher IFN-g secretion than cells from MBP-inoculated mice (950 ± 265.2 pg/ml and 147.3 ± 55.48 pg/ml, respectively). Results indicate that Tc13Tul participation in the innate immune response against T. cruzi is mainly exerted in phenomena related to the evasion of the immune system, such as non-specific Ig production. In contrast, as IFN-g is an important factor involved in T. cruzi resistance, this may be considered a Tc13Tul effect in favor to the host.